Recreation and firearms use as an emerging wildfire risk on western United States National Conservation Lands - Megan R. Dolman; Karen C. Short; Jodi S. Brandt; Mark A. Finney; T. Trevor Caughlin; Megan E. Cattau (Journal of Environmental Management, 2026)

Medically Tailored Grocery Delivery for Food Pantry Clients with Diabetes - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Brett Rowland; Bonnie Faitak; Jazmin Lane; Rosana Solis-Garcia; Holly C. Felix; Krista Langston; Pearl A. McElfish; Juan Mejia-Otera; et al. (Journal of Nutrition Education and Behavior, 2025)

Diet Quality of School Breakfast and Lunch Menus Across Rural Arkansas - E. Short; S. Sorrell; P. Martin; L. Robinson; K. Bounds; B. Rowland; B. Faitak; C. Long (Journal of the Academy of Nutrition and Dietetics, 2025)

Diet Quality Among Community Members With Diabetes and Food Insecurity in Northwest Arkansas: Comparison Across 3 Racial/Ethnic Groups - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Alexandra Diaz-Cruz; Brett Rowland; Holly C. Felix; Krista Langston; Pearl A. McElfish; Christopher R. Long (Journal of Nutrition Education and Behavior, 2025)

Optimizing woody fuel treatments to reduce wildfire risk to sagebrush ecosystems in the Great Basin of the western US - Michelle A. Day; Claire M. Tortorelli; Lisa M. Ellsworth; Karen C. Short; Jessi L. Brown; Sofia Koutzoukis; Julia Olszewski; Alan A. Ager; Jeanne C. Chambers (Journal of Environmental Management, 2025)

Exploring the boundaries of life cycle analysis in environmental hazard assessment - Diana Khripko; Samuel W. Short; Silviu O. Petrovan; David C. Aldridge; Julie Bremner; Andre M. Gomes; David F. Willer (Journal of Cleaner Production, 2025)

Relationships between body length and bony structure measures in North American temperate freshwater fishes - Kamden C. Glade; Jay Holland; Baylor Short; Kendra Fink; Andrew W. Hafs (Journal of Fish Biology, 2025)
Stomach content investigations of piscivorous fishes provide resource managers with valuable information concerning diet patterns, community structure and species interactions. Unique bony structures are often used to identify partially digested prey fish, and recent advancements in molecular techniques have provided increased taxonomic resolution of prey fish remains. However, gravimetric and volumetric methods only account for the partial remains recovered in the sample, which could lead to underestimates of the dietary contributions of digested prey items identified using these techniques. We therefore investigated relationships between total length and bony structures for multiple fish taxa observed in the diets of piscivorous fishes in Minnesota lakes using linear regressions. Cleithra, otoliths, backbone measurements, average vertebrae lengths and ictalurid pectoral spine lengths were used to create equations to estimate total length of digested prey. Predictive equations were developed for families, genera and species, as well as general equations averaged across all taxa. Nearly all equations were statistically significant ( p r 2 ≥ 0.85), although there was substantial variability among taxa and structures. These equations will give investigators an additional tool to maximize the information gained from fish diet studies.

Infant cognitive home environment as a moderator for the association of prenatal lead on child language - Amanda C. Wylie; Michael T. Willoughby; Rebecca C. Fry; W. Roger Mills-Koonce; Sarah J. Short; Cathi B. Propper (NeuroToxicology, 2025)

Evaluation of the Anti-Inflammatory Effects of Novel Fatty Acid-Binding Protein 4 Inhibitors in Microglia - Yi Ling Low; Ethan Kreutzer; Indu R. Chandrashekaran; Luke A. Adams; Jason Pun; Bradley C. Doak; Yijun Pan; Jennifer L. Short; Martin J. Scanlon; Joseph A. Nicolazzo (Journal of Neuroimmune Pharmacology, 2025)
Fatty acid-binding protein 4 (FABP4) is a key lipid binding protein expressed in microglia, which has been demonstrated to play a critical role in microglial-mediated neuroinflammation, a component of many neurodegenerative diseases. Compounds able to inhibit the function of FABP4 have shown promise in reducing microglial-mediated neuroinflammation, however, their physicochemical properties would prevent their ability to be easily formulated and traverse the blood–brain barrier (BBB) in order to access microglial FABP4. To this end, this study assessed the ability of a series of FABP4 inhibitors, with more desirable physicochemical properties, to attenuate microglial inflammation in an in vitro setting. Four inhibitors with varying affinity to FABP4, as measured by isothermal titration calorimetry (MFP-0011462, MFP-0012314, MFP-0012318, and MFP-0012328), were assessed for their ability to induce toxicity and attenuate reactive oxygen species (ROS) generation and tumour necrosis factor-α (TNF-α) release from lipopolysaccharide (LPS)-activated BV-2 microglia. All FABP4 inhibitors were determined to be soluble in the aqueous buffers at the highest concentration used in the assays (100 µM). Isothermal titration calorimetry demonstrated that the compounds had varying affinities for FABP4 (K D values of 316 nM to > 100 µM). The ability of FABP4 inhibitors to reduce LPS-mediated ROS production aligned with their K D for FABP4, with the most effective inhibitor (MFP-0012328) also able to reduce TNF-α production (by RT-qPCR) and TNF-α release from LPS-activated BV-2 cells by 17% and 25%, respectively. These studies have demonstrated that a series of FABP4 inhibitors with more appropriate physicochemical properties for BBB penetration are able to reduce microglial-mediated inflammation, which may be of benefit in diseases where overactivation of microglia leads to neurodegeneration.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Mapping hazards to the global food system - David F. Willer; Samuel Short; Diana Khripko; Silviu O. Petrovan; Alec P. Christie; Julie Bremner; William J. Sutherland; David C. Aldridge (Environmental Monitoring and Assessment, 2024)
Environmental hazards associated with the global food system threaten societal integrity. Yet, there is a major data gap in the global understanding of how the prevalence of hazards is changing over time, how different classes of hazard are distributed, and whether the combined literature represents hazard prevalence equitably across research, policy and legislation, and news. Here, we explore this data gap, leveraging global research, policy, and news databases. We reveal increasing attention on food system hazards over time, in line with major geopolitical events. Coverage on environmental hazards is not distributed equally geographically, and media attention does not match research and policy evidence focus. Climate change and water scarcity in particular receive substantial attention across all source types, whilst, for example biodiversity loss, genetic erosion, or harmful algal blooms receive much less. Environmental, financial and food systems sustainability damage due to hazard neglect should be avoided and a first step is to understand, map, and quantify biases in focus.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Disentangling drivers of annual grass invasion: Abiotic susceptibility vs. fire-induced conversion to cheatgrass dominance in the sagebrush biome - Alexandra K. Urza; David I. Board; John B. Bradford; Jessi L. Brown; Jeanne C. Chambers; Daniel R. Schlaepfer; Karen C. Short (Biological Conservation, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

The added value of simulated near-surface wind speed over the Alps from a km-scale multimodel ensemble - M. O. Molina; J. M. Careto; C. Gutiérrez; E. Sánchez; K. Goergen; S. Sobolowski; E. Coppola; E. Pichelli; N. Ban; D. Belus̆ić; C. Short; C. Caillaud; et al. (Climate Dynamics, 2024)
The advancement of computational resources has allowed researchers to run convection-permitting regional climate model (CPRCM) simulations. A pioneering effort promoting a multimodel ensemble of such simulations is the CORDEX Flagship Pilot Studies (FPS) on “Convective Phenomena over Europe and the Mediterranean” over an extended Alps region. In this study, the Distribution Added Value metric is used to determine the improvement of the representation of all available FPS hindcast simulations for the daily mean near-surface wind speed. The analysis is performed on normalized empirical probability distributions and considers station observation data as the reference. The use of a normalized metric allows for spatial comparison among the different regions (coast and inland), altitudes and seasons. This approach permits a direct assessment of the added value between the CPRCM simulations against their global driving reanalysis (ERA-Interim) and respective coarser resolution regional model counterparts. In general, the results show that CPRCMs add value to their global driving reanalysis or forcing regional model, due to better-resolved topography or through better representation of ocean-land contrasts. However, the nature and magnitude of the improvement in the wind speed representation vary depending on the model, the season, the altitude, or the region. Among seasons, the improvement is usually larger in summer than winter. CPRCMs generally display gains at low and medium-range altitudes. In addition, despite some shortcomings in comparison to ERA-Interim, which can be attributed to the assimilation of wind observations on the coast, the CPRCMs outperform the coarser regional climate models, both along the coast and inland.

Evolution of avian heat tolerance: The role of atmospheric humidity - Marc T. Freeman; Bianca Coulson; James C. Short; Celiwe A. Ngcamphalala; Mathome O. Makola; Andrew E. McKechnie (Ecology, 2024)
The role of atmospheric humidity in the evolution of endotherms' thermoregulatory performance remains largely unexplored, despite the fact that elevated humidity is known to impede evaporative cooling capacity. Using a phylogenetically informed comparative framework, we tested the hypothesis that pronounced hyperthermia tolerance among birds occupying humid lowlands evolved to reduce the impact of humidity‐impeded scope for evaporative heat dissipation by comparing heat tolerance limits (HTLs; maximum tolerable air temperature), maximum body temperatures ( T b max), and associated thermoregulatory variables in humid (19.2 g H 2 O m −3 ) versus dry (1.1 g H 2 O m −3 ) air among 30 species from three climatically distinct sites (arid, mesic montane, and humid lowland). Humidity‐associated decreases in evaporative water loss and resting metabolic rate were 27%–38% and 21%–27%, respectively, and did not differ significantly between sites. Decreases in HTLs were significantly larger among arid‐zone (mean ± SD = 3.13 ± 1.12°C) and montane species (2.44 ± 1.0°C) compared to lowland species (1.23 ± 1.34°C), with more pronounced hyperthermia among lowland ( T b max = 46.26 ± 0.48°C) and montane birds ( T b max = 46.19 ± 0.92°C) compared to arid‐zone species (45.23 ± 0.24°C). Our findings reveal a functional link between facultative hyperthermia and humidity‐related constraints on evaporative cooling, providing novel insights into how hygric and thermal environments interact to constrain avian performance during hot weather. Moreover, the macrophysiological patterns we report provide further support for the concept of a continuum from thermal specialization to thermal generalization among endotherms, with adaptive variation in body temperature correlated with prevailing climatic conditions.

Maternal prenatal lead levels and neonatal brain volumes: Testing moderations by maternal depressive symptoms and family income - Amanda C. Wylie; Sarah J. Short; Rebecca C. Fry; W. Roger Mills-Koonce; Cathi B. Propper (Neurotoxicology and Teratology, 2024)

Multiple social and environmental factors affect wildland fire response of full or less-than-full suppression - Molly C. Daniels; Kristin H. Braziunas; Monica G. Turner; Ting-Fung Ma; Karen C. Short; Adena R. Rissman (Journal of Environmental Management, 2024)

Movement ecology and minimum density estimates of red foxes in wet grassland habitats used by breeding wading birds - Tom A. Porteus; Mike J. Short; Andrew N. Hoodless; Jonathan C. Reynolds (European Journal of Wildlife Research, 2024)
The red fox ( Vulpes vulpes ) is a widely distributed generalist meso-predator implicated in declines of wading bird populations. In the wet grassland habitats where waders breed, wildlife managers work to mitigate fox predation risk to waders during the nesting period through lethal and non-lethal control methods. However, limited knowledge on fox movement ecology in these habitats makes it difficult to design effective management strategies. We used GPS telemetry to understand fox home range size, daily activity and movement patterns, and how these metrics may vary among wet grassland sites with different management. We caught and GPS-tagged 35 foxes in the March–June wader nesting period on two wet grassland sites in central southern England; Britford during 2016/17 and Somerley during 2018/19. We estimated home range areas from location data using local convex hulls, and from these estimates we derived the minimum fox density at each site and year. Daily activity patterns and movement behaviour of each fox were obtained using both telemetry and trail camera data. Mean fox home range area at Britford (0.21 km 2 , SE = 0.025) was significantly smaller than at Somerley (0.68 km 2 , SE = 0.067), and estimated minimum densities were around four times higher (Britford = 10.6 foxes/km 2 , Somerley = 2.4 foxes/km 2 ). Foxes were more active and moved faster during twilight and night hours, but both telemetry and camera data indicate they were also active for one-third of daylight hours. Distances moved per day were variable between foxes but generally smaller at Britford. We also found evidence for dispersal during spring, with movements of up to 19 km per day. Home ranges at both wet grassland sites were smaller than comparable sites elsewhere. These indicated foxes were living at exceptionally high densities at Britford, where there is no fox control, increased food availability and where waders no longer breed. Spatio-temporal movement patterns were closely related to home range metrics, with higher levels of fox activity at Somerley, where home ranges were larger. The movements of itinerant and dispersing foxes during the nesting period suggests that lethal control would need to be very intensive to be effective. The likely anthropogenic food subsidy of fox density at Britford suggests that controlling access to similar food resources would help reduce predation pressure on breeding waders.

In loving memory of Prof. A.T. Williams: A life dedicated to Coastal Geomorphology, Conservation and Management - Adriana Gracia C.; Andrew Cooper; Andrew Short; Anton Micallef; Ayşen Ergin; Carlos Pereira da Silva; Chris House; Enzo Pranzini; Frank van der Meulen; Julian Orford; Michael Phillips; Omar Alharbi; et al. (Ocean & Coastal Management, 2023)

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Two centuries of water-level records at Lake George, NSW - M. A. Short; R. S. Norman; B. Pillans; P. De Deckker; R. Usback; B. N. Opdyke; T. R. Ransley; S. Gray; D. C. McPhail (Australian Journal of Earth Sciences, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Will Landscape Fire Increase in the Future? A Systems Approach to Climate, Fire, Fuel, and Human Drivers - Karin L. Riley; A. Park Williams; Shawn P. Urbanski; David E. Calkin; Karen C. Short; Christopher D. O’Connor (Current Pollution Reports, 2019)

Valuing and understanding fish populations in the Anthropocene: key questions to address - C. Obregón; A. R. Lyndon; J. Barker; H. Christiansen; B. J. Godley; S. Kurland; J. J. Piccolo; R. Potts; R. Short; A. Tebb; S. Mariani (Journal of Fish Biology, 2018)
Research on the values of fish populations and fisheries has primarily focused on bio‐economic aspects; a more nuanced and multidimensional perspective is mostly neglected. Although a range of social aspects is increasingly being considered in fisheries research, there is still no clear understanding as to how to include these additional values within management policies nor is there a cogent appreciation of the major knowledge gaps that should be tackled by future research. This paper results from a workshop held during the 50th anniversary symposium of the Fisheries Society of the British Isles at the University of Exeter, UK, in July 2017. Here, we aim to highlight the current knowledge gaps on the values of fish populations and fisheries thus directing future research. To this end, we present eight questions that are deeply relevant to understanding the values of fish populations and fisheries. These can be applied to all habitats and fisheries, including freshwater, estuarine and marine.

Pheromone-based decision support tools for management of Halyomorpha halys in apple orchards: development of a trap-based treatment threshold - Brent D. Short; Ashot Khrimian; Tracy C. Leskey (Journal of Pest Science, 2017)

Establishing the behavioral basis for an attract-and-kill strategy to manage the invasive Halyomorpha halys in apple orchards - William R. Morrison; Doo-Hyung Lee; Brent D. Short; Ashot Khrimian; Tracy C. Leskey (Journal of Pest Science, 2016)

Behavioral Responses of the Invasive Halyomorpha halys (Stål) to Traps Baited with Stereoisomeric Mixtures of 10,11-Epoxy-1-bisabolen-3-OL - Tracy C. Leskey; Ashot Khrimian; Donald C. Weber; Jeffrey C. Aldrich; Brent D. Short; Doo-Hyung Lee; William R. Morrison (Journal of Chemical Ecology, 2015)

Drug Access to the Central Nervous System in Alzheimer’s Disease: Preclinical and Clinical Insights - Dharmini C. Mehta; Jennifer L. Short; Sarah N. Hilmer; Joseph A. Nicolazzo (Pharmaceutical Research, 2015)

In-silico QTL mapping of postpubertal mammary ductal development in the mouse uncovers potential human breast cancer risk loci - Darryl L. Hadsell; Louise A. Hadsell; Walter Olea; Monique Rijnkels; Chad J. Creighton; Ian Smyth; Kieran M. Short; Liza L. Cox; Timothy C. Cox (Mammalian Genome, 2015)

Altered Brain Uptake of Therapeutics in a Triple Transgenic Mouse Model of Alzheimer’s Disease - Dharmini C. Mehta; Jennifer L. Short; Joseph A. Nicolazzo (Pharmaceutical Research, 2013)

A simulation of probabilistic wildfire risk components for the continental United States - Mark A. Finney; Charles W. McHugh; Isaac C. Grenfell; Karin L. Riley; Karen C. Short (Stochastic Environmental Research and Risk Assessment, 2011)

Parasporins from a Caribbean Island: Evidence for a Globally Dispersed Bacillus thuringiensis Strain - Eric Gonzalez; Jose C. Granados; John D. Short; David R. Ammons; Joanne Rampersad (Current Microbiology, 2011)

Why replication is important in landscape genetics: American black bear in the Rocky Mountains - R. A. SHORT BULL; S. A. CUSHMAN; R. MACE; T. CHILTON; K. C. KENDALL; E. L. LANDGUTH; M.K. SCHWARTZ; K. MCKELVEY; FRED W. ALLENDORF; G. LUIKART (Molecular Ecology, 2011)
We investigated how landscape features influence gene flow of black bears by testing the relative support for 36 alternative landscape resistance hypotheses, including isolation by distance (IBD) in each of 12 study areas in the north central U.S. Rocky Mountains. The study areas all contained the same basic elements, but differed in extent of forest fragmentation, altitude, variation in elevation and road coverage. In all but one of the study areas, isolation by landscape resistance was more supported than IBD suggesting gene flow is likely influenced by elevation, forest cover, and roads. However, the landscape features influencing gene flow varied among study areas. Using subsets of loci usually gave models with the very similar landscape features influencing gene flow as with all loci, suggesting the landscape features influencing gene flow were correctly identified. To test if the cause of the variability of supported landscape features in study areas resulted from landscape differences among study areas, we conducted a limiting factor analysis. We found that features were supported in landscape models only when the features were highly variable. This is perhaps not surprising but suggests an important cautionary note – that if landscape features are not found to influence gene flow, researchers should not automatically conclude that the features are unimportant to the species’ movement and gene flow. Failure to investigate multiple study areas that have a range of variability in landscape features could cause misleading inferences about which landscape features generally limit gene flow. This could lead to potentially erroneous identification of corridors and barriers if models are transferred between areas with different landscape characteristics.

Seasonal Changes in Hepatic Gene Expression Reveal Modulation of Multiple Processes in Rainbow Smelt (Osmerus mordax) - Robert C. Richards; Connie E. Short; William R. Driedzic; K. Vanya Ewart (Marine Biotechnology, 2010)

Neglect of Genetic Diversity in Implementation of the Convention on Biological Diversity - LINDA LAIKRE; FRED W. ALLENDORF; LAUREL C. ARONER; C. SCOTT BAKER; DAVID P. GREGOVICH; MICHAEL M. HANSEN; JENNIFER A. JACKSON; KATHERINE C. KENDALL; KEVIN McKELVEY; MAILE C. NEEL; ISABELLE OLIVIERI; NILS RYMAN; et al. (Conservation Biology, 2010)

Sensitivity of tropical seabirds to El Niño precursors - Carol A. Devney; Michael Short; Bradley C. Congdon (Ecology, 2009)
Intense El Niño events severely impact seabird populations, often months in advance of peak temperature anomalies. The trophic mechanisms responsible for these impacts are unknown but are assumed to operate at seasonal scales and to be linked to ocean productivity changes. Precursors to El Niño events include changes in both sea‐surface temperature and the depth of the 20°C thermocline. Foraging piscivorous seabirds are known to be sensitive to both thermocline depth and sea‐surface temperature change, but the potential influence of these phenomena on breeding dynamics is unknown. Using 18 years of data on three seabirds of the western tropical Pacific, we show that pelagic seabird breeding participation is directly and independently related to changes in both surface chlorophyll concentration and thermocline depth that occur well in advance of El Niño generated sea‐surface temperature anomalies. In contrast, breeding in an inshore foraging species is not correlated with any environmental/biological parameters investigated. These findings demonstrate that El Niño related phenomena do not affect seabird prey dynamics solely via productivity shifts at seasonal scales, nor in similar ways across different seabird foraging guilds. Our results also suggest that population declines observed in the western tropical Pacific may be directly related to the frequency and intensity of El Niño anomalies over the study period.

Pain Assessment in Animals - A. Bufalari; C. Adami; G. Angeli; C. E. Short (Veterinary Research Communications, 2007)

SeagrassNet monitoring across the Americas: case studies of seagrass decline - Frederick T. Short; Evamaria W. Koch; Joel C. Creed; Karine M. Magalhães; Eric Fernandez; Jeffrey L. Gaeckle (Marine Ecology, 2006)
Seagrasses are an important coastal habitat worldwide and are indicative of environmental health at the critical land–sea interface. In many parts of the world, seagrasses are not well known, although they provide crucial functions and values to the world's oceans and to human populations dwelling along the coast. Established in 2001, SeagrassNet, a monitoring program for seagrasses worldwide, uses a standardized protocol for detecting change in seagrass habitat to capture both seagrass parameters and environmental variables. SeagrassNet is designed to statistically detect change over a relatively short time frame (1–2 years) through quarterly monitoring of permanent plots. Currently, SeagrassNet operates in 18 countries at 48 sites; at each site, a permanent transect is established and a team of people from the area collects data which is sent to the SeagrassNet database for analysis. We present five case studies based on SeagrassNet data from across the Americas (two sites in the USA, one in Belize, and two in Brazil) which have a common theme of seagrass decline; the study represents a first latitudinal comparison across a hemisphere using a common methodology. In two cases, rapid loss of seagrass was related to eutrophication, in two cases losses related to climate change, and in one case, the loss is attributed to a complex trophic interaction resulting from the presence of a marine protected area. SeagrassNet results provide documentation of seagrass change over time and allow us to make scientifically supported statements about the status of seagrass habitat and the extent of need for management action.

Use of the polymerase chain reaction and denaturing gradient gel electrophoresis to study diversity in natural virus communities - S. M. Short; C. A. Suttle (Hydrobiologia, 1999)

Shoot regeneration from cultured root explants of spinach (Spinacia oleracea L.): a system for Agrobacterium transformation - K. A. Knoll; K. C. Short; I. S. Curtis; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

Uranium/thorium dating of ferricretes from mid- to late pleistocene glacial sediments, western Tasmania, Australia - Paul C. Augustinus; Stephen A. Short; Henk Heijnis (Journal of Quaternary Science, 1997)

Responses of channel catfish to xenobiotics: Induction and partial characterization of a mixed function oxygenase - Sue W. Fingerman; Louise A. Brown; Melanie Lynn; Everett C. Short (Archives of Environmental Contamination and Toxicology, 1983)